Analisis Dampak Kelangkaan Pupuk Terhadap Pendapatan Petani Padi Di Desa Kacangan Kabupaten Lamongan - Febby Dany Lestary; Muhammad Yasin (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research was conducted to identify the effect of subsidized fertilizer restrictions on the income and production of lowland rice farmers. The method used is qualitative, with the study population consisting of 6 farmers. The sample was selected using simple random sampling, and the data used for analysis is descriptive data. The results showed that there were differences in farmer income before and after subsidized fertilizer restrictions. Before the restrictions, the average income of farmers reached IDR 12,299,250 per planting season with a total cost of IDR 6,075,750. However, after the restrictions, the average income of farmers decreased to IDR 10,537,083 per planting season, with total costs increasing to IDR 7,838,250 per planting season. In overcoming subsidized fertilizer restrictions, farmers have tried several solutions. However, until 2023, this solution is not yet fully effective. Therefore, the government of Kacangan Village took the initiative to partner with parties who could provide loan capital for rice farming and promote organic farming with the use of natural fertilizers as an alternative. This aims to overcome the constraints of subsidized fertilizer restrictions so that people can temporarily switch to using non-subsidized fertilizers.